2000
DOI: 10.1046/j.1442-200x.2000.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of rotavirus infections in Korea

Abstract: Rotavirus is the most common cause of acute watery diarrhea in young Korean children. Rotavirus vaccine will soon be available, and information is urgently required about the serotype distribution of recent epidemics and clinical characteristics of rotavirus infection in Korean children before the implementation of a vaccination program against rotavirus. We reviewed published studies of the past 20 years, carried out on Korean children with rotavirus gastroenteritis. Rotavirus was estimated to be responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 10 publications
7
51
0
2
Order By: Relevance
“…The highest prevalence was found in April (57/134, 42.5%), followed by March (64/184, 34.8%) and May (21/85, 24.7%), respectively. The results of this study are in agreement with previous findings that group A RoVs were detected more frequently in March and April in Japan (24,25).…”
Section: Discussionsupporting
confidence: 93%
“…The highest prevalence was found in April (57/134, 42.5%), followed by March (64/184, 34.8%) and May (21/85, 24.7%), respectively. The results of this study are in agreement with previous findings that group A RoVs were detected more frequently in March and April in Japan (24,25).…”
Section: Discussionsupporting
confidence: 93%
“…Rotavirus infections occurred almost all year in the south, with less distinct seasonal differences (13,20,23,24). Our results are similar to those of studies conducted in Korea, China, and Thailand but differed from those of a Japanese study, in which rotavirus was rarely detected from September to December (9,20,29,33).…”
Section: Rotavirus Infectionsupporting
confidence: 72%
“…Other studies also showed a low prevalence of rotavirus detection in fecal samples in this group (21,27,31). It was reported that asymptomatic infection with rotavirus was not infrequent, especially in neonates, in whom only mild or subclinical symptoms were seen (17,29). However, most of children infected with rotavirus showed one or several clinical symptoms.…”
Section: Rotavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…구조 단백질들 중 VP6은 inner capsid protein으로 rotavirus들이 공통적으로 가지는 항원 결정기이기 때문에 혈청학 적 진단에 사용되며, A~G 혈청군(group)으로 나누는 기준이 된다. 혈청군 중 A, B, C group만 사람과 동물, 모두에게 질병 을 유발하는데, 이 중 group A rotavirus는 세계적으로 가장 높은 분포를 보인다 [3,7,8,24] …”
Section: 서 론unclassified